InCl3-mediated addition of indole to isatogens: an expeditious synthesis of 13-deoxy-isatisine A - Kumar, Chepuri V. Suneel; Puranik, Vedavati G.; Ramana, Chepuri V. (Chemistry-A European Journal, 2012)
A strategy directed towards the total synthesis of isatisine A that involves several late-stage metal-catalyzed transformations that address the key carboncarbon and carbonheteroatom bond formations has been developed. As a part of this strategy, methods for the addition of indoles to isatogens that lead selectively to either 2,2-disubstituted N-hydroxyindolin-3-one or 2,2-disubstituted indolin-3-one compounds have been developed by employing InCl3 as a catalyst or as the reagent. The present methods provide the first examples of the additions of indoles to the isatogen nucleus. To demonstrate its viability, the synthesis of 13-deoxy-isatisine A has been completed in ten steps from a known and easily available lactone.
Keywords: indium; indoles; isatogens; Natural products; Total synthesis